THE RELATIONSHIP BETWEEN SELF EFFICACY AND MEDICATION COMPLIANCE IN TUBERCULOSIS PATIENT-S AT GARUDA HEALTH CENTER IN BANDUNG CITY IN 2023 - Marselina, Seli; Kusmiran, Eny; Sutisna, Iqbal (Indonesian Journal of Community Health Nursing, 2024)
Introduction. Tuberculosis is an infectious infection that often attacks the lung organs caused bymycrobacterium tuberculosis bacteria. Adherence to medication is a behavior that adheres torecommendations made by health care providers related to timeliness, dosage and frequency of takingmedication. Tuberculosis patients have a treatment time of about 6-9 months, making patients will besaturated with the duration of treatment. One of the psychological factors that affect adherence to takingmedication is self-efficiency. High self-efficacy in a person will have a positive impact and can provideconfidence and confidence in one's own ability to deal with problems.Method. The design of this study is descriptive analytic with a cross sctional approach. This researchinstrument used questionnaires. Data collection using total sampling technique obtained 77 respondents,data analysis using Chi-square test.Results. This study found 25 (32.5%) respondents belonging to the low self-efficacy category with acompliance rate of 14 (18.2%). There was a relationship between self-efficacy and medicationadherence in tuberculosis patients with a p-value of <0.001.Conclusion. It can be concluded that there is a relationship between self-efficacy and adherence totaking medication in tuberculosis patients at the Garuda City Bandung Health Center in 2023. Keywords: Medication Adherence; Self Eficacy; Tuberculosis.